Case Report: Presumptive spinal embryonal tumor in a cat - van den Heuvel, Marieke; Van Koulil, Quinten; Willems, Dorien; Carrera, Ines; Bergmann, Wilhelmina; Rissi, Daniel R.; Santifort, Koen M. (Frontiers in Veterinary Science, 2025)
A 5-year-old male castrated domestic shorthaired cat was presented with asymmetrical, right worse than left, progressive paraparesis, proprioceptive ataxia, and a flaccid tail. Neuroanatomical localization was to the L4-caudal spinal cord segments, nerve roots, and/or spinal nerves worse on the right side. Based on development of clinical signs, the spinal cord segments and/or spinal nerves forming the cauda equina were suspected to have been involved first. Magnetic resonance imaging (MRI) revealed a well-defined lesion extending from the level of the mid-body of L5 to the caudal aspect of L6, slightly heterogeneous, hyperintense in T2W and STIR, mildly hypointense in T1W, and with mild to moderate contrast enhancement. Initial prednisolone treatment (0.6 mg/kg twice daily) failed to result in improvement, and the neurological status worsened. Surgery (L5-L6 dorsal laminectomy) revealed a red, intradural and predominantly extraparenchymal mass that was partly fused with the conus medullaris and spinal nerve roots. Euthanasia was elected intraoperatively after discussion with the owner. Histologically the mass consisted of a poorly demarcated primarily extraparenchymal but also intraparenchymal neoplasm composed of tall, columnar neoplastic cells arranged in rows and pseudostratified patterns aligned perpendicularly to the fibrovascular stroma. Neoplastic cells formed neuroblastic rosettes and pseudorosettes throughout. The mitotic count was 73 in 2.37 mm2 (10 FN22/40X fields). Neoplastic cells had widespread cytoplasmic immunolabeling for PGP9.5 and were negative for pancytokeratin, OLIG2, GFAP, NeuN, NSE, NF, and SYN. Histologic changes were consistent with a presumed embryonal tumor.